Hukum Internasional dalam Konflik Kepentingan Ekonomi Negara Berkembang dan Negara Maju - hikmahanto yuwono (Jurnal Hukum IUS QUIA IUSTUM, 2001)
According todeveloping states perspective, international law'as It stand is essentially the product of Western States and accommodating the developed countries better than the developing ones. This attitudes toward international law could be analyzed with some theories, e.g. Critical Legal Studies. The essence of this theory explains the political power beyond the law making. To strengthen developing countriesin reconstructing the international law, the education in law discipline should prepare many skilled lawyers,legislators, lobbyist etc from the third world.